Production and characterization of sunflower (Helianthus annuus L.) protein enriched products obtained at pilot plant scale - Salgado, Pablo Rodrigo (2012)
Sunflower protein concentrates with different content of phenolic compounds were produced at pilot plant scale from the by-product of oil manufacturing. The products obtained were characterized, and their physicochemical properties (i.e. surface hydrophobicity, thermal stability, and polypeptide composition) were evaluated at different storage conditions. All the procedures evaluated resulted in sunflower protein concentrates with high protein solubility (>60%) but with different chemical composition, color, and physicochemical properties. The products exhibited intense coloration and antioxidant properties due to their residual phenolic compounds content. The addition of an isoelectric precipitation step increased the protein content and the removal of phenolic compounds. The resulting concentrates exhibited high protein digestibility in vitro, even in the presence of phenolic compounds, and maintained high protein solubility for at least 6 months of storage. During this period, only structural changes in proteins were observed, as evidenced by their surface hydrophobicity. The results demonstrate that it is feasible to produce sunflower protein concentrates with high solubility on a pilot plant scale, using sunflower oilcake as starting material.